(untitled) (Journal of the College of Basic Education, 2026)
This research examines the verbal form -af’ala- in Al-Farabi’s Diwan al-Adab, a semantic study that follows this form as it appears in Diwan al-Adab and according to the order of the form therein, extracting each verb in the form -af’ala- where it appears in six places, Then I traced the verb lexically and its uses, and the relationship between the original meaning of the verb and other connotations, arriving at what Al-Farabi mentioned in his book, and clarifying its connotation in the Holy Quran, and what the Hadith interpreted as evidence of the verb’s connotation, where I researched the connotation of the verb and the way it was formulated, and the places where it occurs and the appropriateness of what is said about it.